Comparison between fluoride varnish and nanohydroxyapatite in the remineralisation of active white spot lesions: a prospective clinical study (Research, Society and Development, 2022)
Objective: The initial expression of dental caries, white spot, is still frequent and requires professional care that may or may not be preventive. It is important to carry out research that evaluates different methods of remineralisation of these lesions, both in primary and permanent dentition. Thus, the aim of this study was to compare the remineralisation potential using fluoride varnish and nano-hydroxyapatite toothpaste in split-mouth design. Materials and Methods: For the research, 21 children between 6 and 12 years of age, with active non-cavitated white spots on primary and permanent teeth were selected. As a methodology, the remineralisation procedures were performed in different hemiarchs and each tooth received a different product: fluoride varnish and nano-hydroxyapatite toothpaste, both in 4 sessions, once a week. Results: Were analyzed by a calibrated examiner with no prior knowledge of the applied product; through visual criteria and measurement of white spots in their largest diameter with a digital caliper. Changes in gloss, color, texture and surface integrity were observed. The collected data received statistical treatment by means of the t-Student test, which identified the effectiveness in the reduction and remineralisation of white spots (p